Perancangan Aplikasi Web untuk Pemantauan dan Pengendalian Sistem Panel Surya Berbasis Long Range Wide Area Network (LoRaWAN) - Msy Yustenti Nabila P; Muhammad Arrofiq (Universitas Syiah Kuala, 2021)
Light or sunlight can be converted into electricity using solar panel technology. The measurement process is needed on current and voltage parameters to determine whether a solar panel is working correctly or not. The application of the Internet of Things (IoT) is a suitable method for monitoring efficiency measurements on solar panel performance in real-time by combining several computational components, protocols, and sensors to interact more quickly and help all activities become more efficient. One IoT technology that can work efficiently is the Long Range Wide Area Network (LoRaWAN). LoRa communicates using radio frequencies with a wide coverage range and has a low power consumption level. In this study, the implementation of LoRaWAN technology as a communication protocol between three series of nodes and one gateway in building a solar panel system is then visualized on a web that can monitor currents and voltages in the form of graphs and numbers. Displays notifications when there is a change in the condition of the large voltage from the solar panel can control the state of turning on or off the lights and turning off the whole node, and displaying a history of current and voltage readings. The functionality of the system will later be tested using black-box testing. There was also a distribution of questionnaires to 35 respondents to measure the level of agreement that the system designed was running well.